2018
DOI: 10.1038/s41398-018-0269-5
|View full text |Cite
|
Sign up to set email alerts
|

Extracting stability increases the SNP heritability of emotional problems in young people

Abstract: Twin studies have shown that emotional problems (anxiety and depression) in childhood and adolescence are moderately heritable (~20–50%). In contrast, DNA-based ‘SNP heritability’ estimates are generally <15% and non-significant. One notable feature of emotional problems is that they can be somewhat transient, but the moderate stability seen across time and across raters is predominantly influenced by stable genetic influences. This suggests that by capturing what is in common across time and across raters, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 46 publications
4
30
0
Order By: Relevance
“…Our results confirm that individual differences in childhood anxiety and depression in childhood have a substantial underlying genetic component. In molecular research, the maximum estimate of SNP heritability of internalizing problems from previous research is 14% (Cheesman et al, 2018). The estimates from the current study are close to this, with measured genetic variants explaining 10% of the variance in depressive symptoms (not significant) and 17% of the variance in anxiety symptoms (significant).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirm that individual differences in childhood anxiety and depression in childhood have a substantial underlying genetic component. In molecular research, the maximum estimate of SNP heritability of internalizing problems from previous research is 14% (Cheesman et al, 2018). The estimates from the current study are close to this, with measured genetic variants explaining 10% of the variance in depressive symptoms (not significant) and 17% of the variance in anxiety symptoms (significant).…”
Section: Discussionmentioning
confidence: 99%
“…Using genome‐based restricted maximum likelihood (GREML) analyses, common genetic variants are studied to examine the extent to which genetic similarity between unrelated individuals is associated with phenotypic similarity. The additive genetic effect of measured single nucleotide polymorphisms (SNPs) currently explains up to 14% of variance in stable emotional problems during childhood (Cheesman et al, 2018). In samples that, along with data on offspring genotypes and phenotypes, have data available on parental genotypes, a novel extension of the approach used in GCTA can be applied to additionally estimate the contribution of parental genotype to offspring behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Stable and transient conditions, referred to as ‘trait’ and ‘state’ in other research contexts, are two related and yet distinctive features contributing to individual differences in mood conditions. Recent population-based genetic and predictive modelling studies have revealed that stable manifestations of emotional problems typically have a higher heritability than more transient features(37). Also longitudinal measures, including variability, had a higher predictive power relating to severe forms of behaviour like suicide attempts(38).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore possible that in childhood, heartbeat counting ability may not be fully developed or it may not have reached adult levels of stability. For example, anxiety is only moderately stable across childhood: correlations between measures at different time points are only ∼r =.30 (e.g., Cheesman et al, 2018). In contrast, stability in adulthood is greater, in the region of ∼r = .50 (e.g., Nes, Røysamb, Reichborn-Kjennerud, Harris, & Tambs, 2007) with some evidence that stability increases with age (from around r =.60 in adolescence to r = .80 in adulthood; e.g., Nivard et al, 2015).…”
Section: Tablementioning
confidence: 99%